Multi-Method Study on Risk Assessment Implementation and Youth Outcomes in the Juvenile Justice System, United States, 2013-2018 - Sullivan, Christopher J. ([Verlag nicht ermittelbar], 2020)
To better understand the factors that may help or hinder effective implementation of risk and needs assessments, the Office of Juvenile Justice and Delinquency Prevention (OJJDP) in 2015 launched a study led by the University of Cincinnati to examine the Ohio Youth Assessment System (OYAS) in three states-Arizona, Indiana, and Ohio. The OYAS tools measure risk and needs to inform court decisions as well as the delivery of services and treatment. Researchers collected data through a variety of methods, including in-person interviews with personnel at juvenile justice agencies; web-based surveys; comprehensive case record data for youths assessed by the OYAS; and phone interviews of youth following their case disposition and/or facility release. One of the study's key objectives was to understand how staff perceived the implementation of the OYAS. To assess the impact of the OYAS on youth outcomes--including reduced recidivism and other prosocial behavior and attitudes--the research team analyzed juvenile justice case records and conducted followup interviews with youth. Demographic variables included in this study include the race, gender, age, ethnicity, and level of education of participants.